A história da psicanálise no Brasil nas primeiras décadas do século XX e sua influência na concepção e constituição de saúde mental no país - Machado, Josiane Cantos (2013)
This study presents an overview of the history of psychoanalysis in Brazil and its relationship with the nation‟s history of mental health and psychiatry. The objective is to investigate the influence exercised by psychoanalysis in the newly-established psychiatry and in the conception of mental health during the early decades in the 20th century. In order to accomplish the objective, I will analyze the early works by Brazilian psychiatrists who used the concepts of the Freudian doctrine to understand and promote mental health in our country, as well as a historical outline of the arrival and establishment of psychoanalysis in Brazil, taking the historical, political and social moment into account. The intention is, through these issues, to check how the diffusion of psychoanalysis took place in Brazil through medicine, and how it was perceived by these early professionals, not only the followers, but also its critics. The hypothesis is that psychoanalysis has been appropriated by psychiatrists as a novelty that could assist in the shaping of a Brazilian identity, providing an answer to questions related to race, education and the formation of a new ideal model of individual that would lead the country to the progress its seeks